The effectiveness of self-directed meal replacement-assisted intermittent fasting in adults - Meixian Zhang; Guifeng Shi; Shuang Wang; Xiaoqin He; Tao-Hsin Tung; Yahong Chen; Yafei Ye (BMC Complementary Medicine and Therapies)
Abstract Objective This study examined whether the addition of meal replacement (MR)-assisted intermittent fasting increases the effectiveness of a lifestyle intervention. Methods In a nonrandomized intervention study, overweight and obese participants aged 18 to 60 years were recruited for weight management with MRs or lifestyle intervention alone (LIA) for 8 weeks. The outcomes were the percent change in body weight from baseline to weeks 4 and 8 and the associated changes in body composition (using a bioimpedance analyzer). Generalized estimating equation (GEE) models were used to compare outcomes between groups. Results A total of 126 participants were recruited, and 74 participants in the MR group and 46 participants in the LIA group finished the intervention protocol. The mean age was 35.4 ± 9.7 years, and 75.4% were female. The baseline BMI was 26.6 ± 3.7 kg/m2. At 4 weeks, the percent weight loss in the MR group was 6.3%, whereas it was 4.0% in the LIA group (P < 0.001). At 8 weeks, the percent weight loss in the MR group was 8.2%, whereas it was 5.8% in the LIA group (P = 0.004). The GEE models revealed no further differences in weight loss or related measurements between the groups, whereas the time effect was significant. Conclusions Our study demonstrated that lifestyle interventions can result in weight loss regardless of the use of MR-assisted intermittent fasting. This finding suggests that nutritional support needs to be provided during short-term weight loss interventions. Trial registration Chinese Clinical Trial Registry number: ChiCTR2500099520, Retrospectively registered 25 March 2025.